2016
DOI: 10.1186/s12967-016-1079-2
|View full text |Cite
|
Sign up to set email alerts
|

AQP5-1364A/C polymorphism and the AQP5 expression influence sepsis survival and immune cell migration: a prospective laboratory and patient study

Abstract: BackgroundThe C-allele of the aquaporin (AQP5) -1364A/C polymorphism is associated with decreased AQP5 expression but increased 30-day survival in patients with severe sepsis. AQP5 expression might affect survival via an impact on cell migration. Consequently, we tested the hypothesis that (1) Aqp5 knockout (KO) compared to wild type (WT) mice show an increased survival following lipopolysaccharide (LPS) administration, and that (2) AQP5 expression and the AQP5 -1364A/C polymorphism alters immune cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…This, in turn, may orchestrate deleterious effects on the kidney, e.g., by renal capillary plugging and micro-thrombi [33]. Certainly, AQP5 significantly impacts upon key mechanisms of inflammation that prevail in sepsis, including immune cell migration and proliferation [13,14]. AQP5 expression facilitates cell movement by transient formation of membrane protrusions via water entry (lamellipodia and membrane ruffles) [14], and target-oriented human neutrophil migration is faster and more frequent with increased AQP5 expression in the AA genotype of the AQP5 -1364A/C SNP [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, may orchestrate deleterious effects on the kidney, e.g., by renal capillary plugging and micro-thrombi [33]. Certainly, AQP5 significantly impacts upon key mechanisms of inflammation that prevail in sepsis, including immune cell migration and proliferation [13,14]. AQP5 expression facilitates cell movement by transient formation of membrane protrusions via water entry (lamellipodia and membrane ruffles) [14], and target-oriented human neutrophil migration is faster and more frequent with increased AQP5 expression in the AA genotype of the AQP5 -1364A/C SNP [13].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, AQP5 significantly impacts upon key mechanisms of inflammation that prevail in sepsis, including immune cell migration and proliferation [13,14]. AQP5 expression facilitates cell movement by transient formation of membrane protrusions via water entry (lamellipodia and membrane ruffles) [14], and target-oriented human neutrophil migration is faster and more frequent with increased AQP5 expression in the AA genotype of the AQP5 -1364A/C SNP [13]. Since C-allele carriers are associated with a lower AQP5 expression in sepsis compared to the AA genotypes [16], the AC/CC genotypes may confer an altered immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, cells were incubated with 50 μM 5-Aza-2′-deoxycytidine (ADC) for three days and, after culture medium change, with 10 μM ADC for an additional three days. Our previous studies indicated that a seven day incubation period is required for efficient demethylation of promoters [ 9 ]. In addition, we investigated the impact of bacterial cell wall components on NFKB1 promoter methylation.…”
Section: Methodsmentioning
confidence: 99%
“…AQP5 is mainly located on the membrane of type I alveolar epithelial cells and has the function of maintaining the water balance of cells [8][9][10]. Studies have shown that AQP5 is associated with different diseases [11][12][13]. For example, it has been reported that AQP5 plays an important role in the elimination of extravascular lung water, and the increase of AQP5 can contribute to lung injury in patients with sepsis [10].…”
Section: Introductionmentioning
confidence: 99%